2007
DOI: 10.4049/jimmunol.178.6.3612
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of an Unfolded Protein Response Impairs MHC Class I Expression

Abstract: HFE C282Y is an example of a mutant protein that does not fold correctly, is retained in the endoplasmic reticulum, and was found previously to diminish surface expression of MHC class I (MHC-I). We now show that its expression in 293T cells triggers an unfolded protein response (UPR), as revealed by the increased levels of H chain binding protein, GRP94, and C/EBP homologous protein. Elevated levels of these proteins were also found in HFE C282Y homozygous PBMCs. Following the UPR induction, a decrease in MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
77
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 44 publications
4
77
1
1
Order By: Relevance
“…38,39 The common human HFE C282Y (murine C294Y) disease-causing mutation alters the secondary structure of HFE, rendering it unable to reach the cell surface, 10 and induces UPR and ER stress in cell culture systems. 40 To test the hypothesis that it might have a similar effect in vivo, we created TTR-Hfe C294Y transgenic animals (Hfe C294Y , Figure 3A) and analyzed parameters of iron metabolism. We bred Hfe C294Y transgenic animals to Hfe Ϫ/Ϫ mice of the same genetic background, and compared Hfe Ϫ/Ϫ mice carrying the Hfe C294Y transgene to Hfe Ϫ/Ϫ littermates.…”
Section: Overexpression Of Hfe or Hfe Mutant Proteins Does Not Initiamentioning
confidence: 99%
See 2 more Smart Citations
“…38,39 The common human HFE C282Y (murine C294Y) disease-causing mutation alters the secondary structure of HFE, rendering it unable to reach the cell surface, 10 and induces UPR and ER stress in cell culture systems. 40 To test the hypothesis that it might have a similar effect in vivo, we created TTR-Hfe C294Y transgenic animals (Hfe C294Y , Figure 3A) and analyzed parameters of iron metabolism. We bred Hfe C294Y transgenic animals to Hfe Ϫ/Ϫ mice of the same genetic background, and compared Hfe Ϫ/Ϫ mice carrying the Hfe C294Y transgene to Hfe Ϫ/Ϫ littermates.…”
Section: Overexpression Of Hfe or Hfe Mutant Proteins Does Not Initiamentioning
confidence: 99%
“…Alternatively, it has been shown that basic amino acids immediately after the transmembrane domain of membrane proteins are necessary for proper insertion and topology. 32 Thus, it is possible that loss of these amino acids in the Hfe ⌬CD truncated protein leads to improper or decreased membrane insertion causing a diminution in protein activity at the cell membrane.Overexpression of mutant HFE in cell culture triggers an unfolded protein response (UPR) 40 and ER stress can induce hepcidin production. 38,39 Using 2 separate methods we were unable to detect ER stress in any of the HFE overexpressing animals, including animals overexpressing an ortholog of the common C282Y human missense mutation that has been shown to induce ER stress in cell culture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In other tissues, mutations in genes encoding secretory pathway proteins have been found to cause endoplasmic reticulum (ER) stress and subsequent activation of the unfolded protein response (UPR), a set of evolutionarily conserved signaling pathways activated upon ER stress (22)(23)(24)(25)(26)(27)(28). UPR has been implicated in the pathogenesis of many conformational diseases, such as Alzheimer disease, Parkinson disease, and diabetes, and is being investigated in many others (29 -33).…”
mentioning
confidence: 99%
“…2016. 46: 929-940 reported in the overexpression model of a mutant HFE protein, which does not fold properly in the ER [36]. In this study, we set up a biochemical assay combined RP-HPLC fractionation with T-cell hybridoma response, which allowed us to quantify the produced amount of the OVA peptide in the cells exposed to hypoxia alone, glucose-deprivation alone, or both hypoxia and glucose deprivation.…”
mentioning
confidence: 99%